IMPLEMENTATION OF SMART TECHNOLOGY, ARTIFICIAL INTELLIGENCE, ROBOTICS, AND ALGORITHMS (STARA): A THREAT OR OPPORTUNITY FOR WORKERS 'FUTURE - Lestari, Lela; Djastuti, Indi (International Business Management - Universitas Ciputra, 2020)
This qualitative phenomenological study aims to examine andcompare the perceptions of workers in the banking sector regarding theimplementation of STARA in their work. This study was conducted throughin-depth interviews with informants about perceptions regarding optimizing STARA implementation in the banking sector, in the form of bankingdigitalization in the current Industrial Revolution 4.0 era. The informantsin this study were bank employees such as the teller, customer service, andback-office personnel. Sampling was done using non-random samplingmethod with purposive sampling technique which amounted to 12 informants, consisting of four tellers, four customer service officers, and fourback-office personnel. The results of the study showed that the majority ofbank employees in frontliner positions, namely tellers, felt that their position could be replaced by the implementation of STARA. However, someinformants in the frontliner position, namely customer service, stated thatthey did not feel threatened, because they believed there was a certaincomfort when customers were served by humans rather than by machines.Meanwhile, bank employees in the back-office position have not felt anythreat due to the implementation of STARA because they feel that the analysis process cannot be fully carried out properly by a system and still requires humans. In addition, employees in the back-office position statedthat the implementation of STARA makes it easy for them to completetheir work and can be used as an opportunity to achieve work performance.The results of this study also show that overall employees have not felt adecrease in commitment to the organization, obstacles in career advancement, desire to move, cynicism, or depression when working with the implementation of STARA, which is predicted to take their jobs.